Efficacy and safety of tocilizumab and baricitinib among patients hospitalized for COVID-19: a systematic review and meta-analysis - Zhang, Jin; Fan, Xiongxiong; Zhang, Xiaoyu; Jiang, Fengli; Wu, Yiping; Yang, Beibei; Li, Xinghuan; Liu, Dong (Frontiers in Pharmacology, 2023)
Introduction:Tocilizumab and baricitinib are recommended treatment options for COVID-19 patients with hyperinflammatory response; however, there is a lack of systematic review directly evaluating their efficacy and safety.Objective:This review was conducted to evaluate the efficacy and safety of tocilizumab and baricitinib in the treatment of hospitalized patients with COVID-19.Methods: Relevant databases were searched for studies that compared the effect or safety of baricitinib or tocilizumab in hospitalized patients with COVID-19. The mortality was the main outcome. The hospital length of stay or adverse drug reactions were taken into consideration as secondary endpoints. The analyses were performed in Revman 5.3 or Stata 16.0. The protocol and analysis plan were pre-registered in PROSPERO, with the registration number CRD42023408219.In total, 10 studies with 2517 patients were included. The overall pooled data demonstrated that, there was no statistically significant difference in the 28-day mortality rate and the hospital length of stay between the tocilizumab and baricitinib (OR= 1.10, 95% CI= 0.80-1.51, P =0.57; OR=-0.68, 95% CI= -2.24-0.87, P= 0.39). The adverse reactions including secondary infection rate, thrombotic and bleeding events, and acute liver injury of tocilizumab were significantly higher than that of baricitinib.